فعالية الوسائط المتعددة فى التحصيل الدراسى والاتجاه نحوها لدى طالبات الصف الأول الثانوى - السبيعي، منى بنت حميد رميزان (جامعة طيبة - كلية التربية, 2009)
تهدف الدراسة إلى التعرف على فعالية استخدام الوسائط المتعددة في تنمية التحصيل لدى طالبات الصف الأول الثانوي واتجاهاتهن نحوها بمكة المكرمة. \ ولتحقيق ذلك استخدمت الباحثة المنهج التجريبي وتم تحديد مجموعتين إحداهما تجريبية قوامها (31) طالبة، والأخرى ضابطة قوامها (33) طالبة، أعدت برمجية في النظرية الذرية الحديثة مستعينة بوسائط محددة (النص المكتوب، الرسوم، الصور الثابتة والمتحركة والفيديو)، وكذلك اختباراً تحصيلياً ومقياساً للاتجاه نحو الوسائط. وبعد التأكد من تقنين أدوات الدراسة، طبقت التجربة على عينة الدراسة، ثم تمت معالجة البيانات التي تم الحصول عليها باستخدام بعض الأساليب الإحصائية كاختبار (ت)، وتحليل التباين المصاحب، ومعامل ارتباط بيرسون. \ وقد كشفت نتائج الدراسة عن أن استخدام الوسائط المتعددة في تعلم الكيمياء أدى إلى تنمية التحصيل الدراسي ككل وعند مستويات المجال المعرفي المختلفة (التذكر، الفهم، التطبيق)، وعن أن استخدام الوسائط المتعددة في تعلم الكيمياء ينمي الاتجاهات الإيجابية للطالبات نحو الوسائط المتعددة. كما أثبتت الدراسة عدم وجود ارتباط موجب بين استخدام الوسائط المتعددة وتنمية التحصيل الدراسي لدى طالبات المجموعة التجريبية. \ وفي ضوء ما توصلت إليه الدراسة من نتائج تم تقديم مجموعة من التوصيات أهمها: تفعيل استخدام الوسائط المتعددة في تدريس بعض موضوعات الكيمياء المناسبة لطبيعة هذه الاستراتيجية، مما يحقق ويثري التنوع في طرق تدريس الكيمياء، وينمي التحصيل، ويفعل استخدام التقنية (الحاسب الآلي). The study aims at the recognize the efficiency of using multimedia aids by first year secondary female students in learning chemistry, and it's effects on their academic achievement and attitudes towards them in the holy city of Makkah . \ To achieve this aim the study used two groups: experimental group with thirty one students, and a control one with thirty three students. A software of the modern atomic theory, Selected aids (written text, drawings and paintings: fixed and movable photos and video), an achievement test and an attitude measurement towards the use of multimedia aids were prepared. \ When the study tools were ready, an experiment on the sample was carried out. The data obtained from the experiment were dealt with using statistical methods such as: T-tests, analysis of c-variant (Ancova) and Person's correlation factor. \ The findings of the experiment illustrated that the use of the multimedia aids in learning chemistry leads to development of academic achievement in the rate of the students as a whole and the different levels of cognitive domains: remembering, comprehension, application. \ The use of the multimedia aids in learning chemistry develops students' positive attitudes towards the aids themselves. The study also proved that there is not any positive correlation between the use of multimedia aids and the development of students academic achievement of the experimental group \ According to the study findings, some recommendations have been offered. Activating the use of multimedia in teaching some chemistry topics that are suitable to the nature of this strategy; this will actualize and enrich the teaching methods of chemistry.
Keywords: طرق التدريس -- الكيمياء -- الوسائط المتعددة -- التحصيل الدراسى -- الصف الأول الثانوى -- مكة المكرمة